In Vitro Rapid Multiplication Protocol for Ex Situ Conservation of the Rare, Endemic Medicinal Plant Achyranthes coynei - Desai, Mayuri; Hurkadale, Pramod J.; Upadhya, Vinayak; Sailo, Lalrinsangi; Hegde, Harsha V.; Pai, Sandeep R. (Planta Medica Letters, 2016)
Achyranthes coynei is a rare, endemic species with potential medicinal properties. The present study aimed to develop an efficient in vitro rapid multiplication protocol for A. coynei. It was successfully propagated in vitro using apical shoot tips as explants. A combination of 6-benzylaminopurine (3.0 mg · L−1), thidiazuron (0.5 mg · L−1), and kinetin (0.5 mg · L−1) in MS basal proved best for multiple shoot induction, yielding 4.8 shoots per explant after 60 days of culture. The shoots were rooted with a frequency of 80 % after 30 days of culture on MS agar medium fortified with IBA/NAA (0.5 mg · L−1) before being acclimatized in the greenhouse. The developed protocol will serve as a tool to restore the rare status of the plant and will append its sustainable utilization.
Keywords: Achyranthes coynei; Amaranthaceae; in vitro; rapid multiplication; kinetin